The impact of bariatric surgery on gut microbiota: a bibliometric analysis of research trends and scientific contributions - Gong, Shuaichang; Zhang, Xiabiao; Chen, Xiaoliang; Wan, Ping; Zhou, Longfei; Zhang, Jun (Frontiers in Microbiology, 2025)
BackgroundObesity is a prevalent global disease closely linked to various chronic conditions. Bariatric surgery (BS) is currently recognized as the most effective treatment. Increasing evidence suggests that BS alters the gut microbiota (GM), which plays a crucial role in postoperative weight loss. However, there has been no systematic bibliometric analysis exploring the relationship between BS and GM to date.MethodsWe conducted a literature search on BS and GM from January 1, 1981, to May 25, 2024, within the Web of Science Core Collection (WoSCC). We utilized Excel 2021, VOSviewer 1.6.19, CiteSpace 6.2.R3, and the R package “bibliometrix” 4.3.0, along with the online bibliometric analysis platform (https://bibliometric.com/app), to visualize publishing trends and research hotspots in this field.ResultsA total of 2,542 articles meeting the criteria were included. Since 2015, the rate of publication has significantly accelerated. The United States leads in both the number of publications and average citations per article. The University of São Paulo is the most active institution, whereas the University of Copenhagen has the highest average citation count. Obesity Surgery is the journal with the highest number of publications, and the most prolific author is Karine Clement. Keyword and thematic analyses indicate that “gut microbiota” and “bariatric surgery” are the primary research hotspots for future studies.ConclusionIn summary, this field is garnering increasing attention. Our findings suggest that future research will likely focus on the effects of bariatric surgery on gut microbiota and its biological mechanisms, the role of gut microbiota in the weight loss process, and the development of combined treatments based on gut microbiota.